2018
DOI: 10.5897/ajmr2018.8868
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological quality of fruit juices sold in cafes and restaurants of Shewarobit town, Amhara, Ethiopia

Abstract: Fresh and unpasteurized fruit juice is common in restaurants, cafeteria, hotels and juice house of Ethiopian cities. Most fruit juices contain sufficient nutrients that could support microbial growth. The current investigation was carried out to investigate the microbiological quality and processing conditions of fruit juice vended in Shewarobit town. Purposive sampling technique was employed to collect sixteen fruit juice samples comprising of eight avocado and eight papaya from five cafeterias and three rest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Microbiology Insights conducted in Hossana Town, Ethiopia, reported none of the food handlers trained in food hygiene and safety. 4 Prevalence of selected bacterial species 26 The presence of Staphylococcus count in fruit juices above 3.0 log CFU/mL is potentially hazardous to human health. 24 However, the current study found 58 (74.4%) of fruit juice samples contaminated with Staphylococcus higher than the maximum permitted level of Gulf standard 2000 that was consistent with the finding of another study conducted in India that found 73.3% of fruit juice samples contaminated with Staphylococcus higher than the recommended standard.…”
mentioning
confidence: 99%
“…Microbiology Insights conducted in Hossana Town, Ethiopia, reported none of the food handlers trained in food hygiene and safety. 4 Prevalence of selected bacterial species 26 The presence of Staphylococcus count in fruit juices above 3.0 log CFU/mL is potentially hazardous to human health. 24 However, the current study found 58 (74.4%) of fruit juice samples contaminated with Staphylococcus higher than the maximum permitted level of Gulf standard 2000 that was consistent with the finding of another study conducted in India that found 73.3% of fruit juice samples contaminated with Staphylococcus higher than the recommended standard.…”
mentioning
confidence: 99%
“…However, another study conducted in Ethiopia found a microbial count in the juice samples ranged from 4.0 to 5.46 log CFU/mL. 15 Furthermore, the study found the mean TVBC in mango, avocado, papaya, and mixed juices was 5.15, 5.44, 5.44, and 5.46 log CFU/mL, respectively. This indicates that about an equal bacterial load was observed among all types of juice samples.…”
Section: Discussionmentioning
confidence: 95%
“…Similarly, the number of fruit juice vending houses serving different types of fresh fruit juices are increasing in Ethiopia. 15 However, the lack of an adequate food safety system is a major problem and has become an obstacle to sustainable health, safety, and economic development of the population of Ethiopia. A study conducted in Ethiopia reported the prevalence of food borne pathogen 2 Environmental Health Insights accounted 8.0% (Salmonella, pathogenic Escherichia coli, Shigella, and Campylobacter spp.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations